2013
DOI: 10.1016/j.repc.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of mesenteric ischemia in a patient with cardiac myxoma

Abstract: Symptoms related to peripheral embolism are experienced in 2%-15% of cases of cardiac myxoma. We present a rare case of a 54-year-old man admitted due to sudden abdominal pain. A computed tomography (CT) scan showed occlusion of the superior mesenteric artery (SMA). As the patient's response to support treatment was favorable, a non-invasive approach was adopted, with prescription of oral anticoagulation (OAC) therapy. Transesophageal echocardiography revealed a tumor in the left atrium. The cardiac mass was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Only 2 reports have described embolization of a cardiac tumor to the small bowel. 7 , 8 The distinguishing feature in our case is the matching histology of the SMA tumor embolus and the excised cardiac tumor, showing a rare, undefined cardiac sarcoma. Matching biopsies to confirm embolization were unavailable in prior case reports.…”
Section: Discussionmentioning
confidence: 60%
“…Only 2 reports have described embolization of a cardiac tumor to the small bowel. 7 , 8 The distinguishing feature in our case is the matching histology of the SMA tumor embolus and the excised cardiac tumor, showing a rare, undefined cardiac sarcoma. Matching biopsies to confirm embolization were unavailable in prior case reports.…”
Section: Discussionmentioning
confidence: 60%
“…Symptoms related to peripheral embolism are experienced in 2–15% of cases. Cases of mesenteric embolism are extremely rare 2. Retrospective studies have shown that histological cardiac tumour is an independent predictor of an embolic event.…”
Section: Descriptionmentioning
confidence: 99%